2016
DOI: 10.9734/bjast/2016/23529
|View full text |Cite
|
Sign up to set email alerts
|

Development of Pedal Operated Honey Extractor

Abstract: Bees are winged insects that produce honey by their activities with the nectar of flowers. The honey produced is sweet and are finding replacement for sugar nowadays. Honey bees live in hives where the honey combs being formed by the bees are being deposited. Various methods had been exploited in extracting this honey from the honey comb both traditionally and by different designs of extractors from the primitive to a modern one. Although the former design which was locally produced in Nigeria was hand driven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…The total number of traditional hives owned (3,647) viz the modern hives owned (1,139) by the respondents in this study, is an indication that more people used traditional beehives than modern hives. Traditional hives were more in areas where beekeeping had been practiced over a long period of time, while in the areas where respondents had practiced beekeeping for a short period, modern hives were the most preferred.…”
Section: Type Of Bee Hives Ownedmentioning
confidence: 66%
See 1 more Smart Citation
“…The total number of traditional hives owned (3,647) viz the modern hives owned (1,139) by the respondents in this study, is an indication that more people used traditional beehives than modern hives. Traditional hives were more in areas where beekeeping had been practiced over a long period of time, while in the areas where respondents had practiced beekeeping for a short period, modern hives were the most preferred.…”
Section: Type Of Bee Hives Ownedmentioning
confidence: 66%
“…Bees are winged, flower-feeding insects with branched body hairs classified under phylum Arthropoda, class Insecta, and order Hymenoptera [1]. The order constitutes diverse species of bees, wasps, ants, and sawflies.…”
Section: Introductionmentioning
confidence: 99%
“…However, Akinnuli et al [4] observed that the traditional method of extracting honey leads to reduction in its nutritional value and quality detected by Babajide et al [2] and Vallianou et al [3]. This was because the unripe and capped honeycomb are collected at night and the extraction is achieved by squeezing manually with the hand.…”
Section: Introductionmentioning
confidence: 99%
“…As discovered by Akinwumi et al [4], different types of honey extractors such as tangential, radial and electrical driven have been developed in advanced countries like Italy, Germany, Australia, United States of America and Turkey. But the cost of purchase, importation and the technical knowhow are making peasant farmers in Nigeria not to have access to them, hence they extract their honey traditionally [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation